1997
DOI: 10.1038/sj.onc.1200806
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity on murine chromosome 6 in two-stage carcinogenesis: evidence for a conserved tumor suppressor gene

Abstract: We have recently demonstrated that loss of heterozygosity (LOH) at 7q31 is frequent in many kinds of human primary tumors and that introducing a single human chromosome (hchr) 7 into a murine squamous cell carcinoma (SCC)-derived cell line suppresses the malignant phenotype. To investigate whether the putative tumor suppressor gene on hchr 7 is conserved in mice, we studied LOH on mouse chromosome (mchr) 6 in chemically induced SCCs in (C57BL6DBA2) F1 (B6D2F1) females. LOH analysis was performed by polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
(25 reference statements)
3
26
0
Order By: Relevance
“…We only observed a 29% LOH (eight of 28 informative cases) rate for D7S522. This was similar to the results of Kerr et al (1996) (34%) but di ers from the results of Zenklusen et al (1995b) who reported 73% LOH detection (14 of 19 informative cases) in D7S522. The discrepancy between our results and those of Zenklusen et al (1995b) may be due to the total number of informative cases and cases of di erent stages and grades that were examined.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We only observed a 29% LOH (eight of 28 informative cases) rate for D7S522. This was similar to the results of Kerr et al (1996) (34%) but di ers from the results of Zenklusen et al (1995b) who reported 73% LOH detection (14 of 19 informative cases) in D7S522. The discrepancy between our results and those of Zenklusen et al (1995b) may be due to the total number of informative cases and cases of di erent stages and grades that were examined.…”
Section: Discussionsupporting
confidence: 89%
“…Zenklusen et al (1995b) examined LOH in chromosome 7q in 26 primary ovarian carcinomas using 14 (C-A)n microsatellite repeats. All 26 cases exhibited LOH at one or more loci on 7q with 73% LOH detected in D7S522 at 7q31.1.…”
Section: Introductionmentioning
confidence: 99%
“…We have mapped CAVEOLIN-1 to human chromosome 7q31.1, as a candidate for a multi-tissue tumour suppressor gene that has been localized to this subchromosomal region . Like CAVEOLIN-1, this tumour suppressor gene is also conserved in mouse (Zenklusen et al, , 1997. Incidences of LOH of over 80% have been detected in breast carcinomas (Zenklusen et al, 1994a), implying that the chromosome 7-tumour suppressor gene is the most frequently inactivated target during breast Lee et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report the mapping of the gene encoding Caveolin-1 to human chromosome 7q31, in proximity to the marker D7S522, which has been mapped to q31.1. A number of studies has revealed a high incidence of loss of heterozygosity (LOH) at 7q31 in a broad range of human tumours, including carcinomas of the breast (Bieche et al, 1992;Zenklusen et al, 1994a), colon (Zenklusen et al, 1995a), kidney (Shridhar et al, 1997), ovary (Kerr et al, 1996;Koike et al, 1997;Zenklusen et al, 1995b), pancreas (Achille et al, 1996), prostate (Takahashi et al, 1995;Zenklusen et al, 1994b), and stomach (Kuniyasu et al, 1994), as well as squamous cell carcinomas of the head and neck (Zenklusen et al, 1995a, Loughran et al, 1997. The highest frequency of LOH was observed at D7S522.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown frequent LOH of microsatellite markers on the long arm of chromosome 7, speci®cally at band q31 in several types of tumor including breast (Devilee et al, 1997;Lin et al, 1996;Zenklusen et al, 1994a), ovarian (Koike et al, 1997;Zenklusen et al, 1995a), pancreatic (Achille et al, 1996), prostatic (Oakahashi et al, 1995;Zenklusen et al, 1994b), and squamous cell carcinoma of the head and neck (Zenklusen et al, 1995b). One microsatellite marker, D7S522, has been described as the most frequently deleted marker in many di erent tumor types (Achille et al, 1996;Devilee et al, 1997;Zenklusen et al, 1994a).…”
Section: Introductionmentioning
confidence: 99%